Long axial field of view PET/CT in critically ill patients: lessons from a case report - van Snick, J. H.; van Leer, B.; Nijsten, M. W. N.; Pillay, J.; Slart, R. H. J. A.; Glaudemans, A. W. J. M.; van Rijsewijk, N. D. (Frontiers in Medicine, 2024)
The introduction of new long axial field of view (LAFOV) scanners is a major milestone in positron emission tomography/computed tomography (PET/CT) imaging. With these new systems a revolutionary reduction in scan time can be achieved, concurrently lowering tracer dose. Therefore, PET/CT has come within reach for groups of patients in whom PET/CT previously was undesirable. In this case report we discuss the procedure of a continuous bed motion (CBM) total-body [ 18 F]FDG PET/CT scan in an intensive care patient. We emphasize the clinical and technical possibilities with this new camera system, a matched clinical protocol, and the added value of a dedicated team.